Total quality management in higher education institutions - Orozco Carrillo, Juan Pablo (2020)
Higher education plays an important role in the cultural and economic development of countries. For several years now, universities, as well as educational systems, have established themselves as forces and agents of development change within their societies. The developed nations of the United States, Europe, the United Kingdom, Australia and Jordan are among the pioneering nations in higher education because of their credibility; therefore a number of students from other Arab, Asian and other nations come to study in these countries. During the period of the last ten years, diverse, innovative, improved, improved, results, best practices and academics, as well as better results, as well as the ability to compete, constantly, through successive events. Understanding the importance of this segment for cultural and socioeconomic development and this requires exceptional government, along with the provision of services, however, the higher education system within those countries will be redesigned, the forces must be sustained, without However, the weaknesses, be managed and developed, to serve a new social order, to meet the persistent needs and to respond to a context of new opportunities and realities.